2005
DOI: 10.1186/1472-6963-5-20
|View full text |Cite
|
Sign up to set email alerts
|

Cost savings associated with improving appropriate and reducing inappropriate preventive care: cost-consequences analysis

Abstract: BackgroundOutreach facilitation has been proven successful in improving the adoption of clinical preventive care guidelines in primary care practice. The net costs and savings of delivering such an intensive intervention need to be understood. We wanted to estimate the proportion of a facilitation intervention cost that is offset and the potential for savings by reducing inappropriate screening tests and increasing appropriate screening tests in 22 intervention primary care practices affecting a population of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 36 publications
0
49
0
Order By: Relevance
“…This fi nding is consistent with a prior estimate by Hogg and colleagues for a facilitation intervention to improve preventive services. 12 Approximately 47% of the total practice facilitation costs were attributable to practice assessment and start-up activities, with another 25% attributable to facilitation visits. Although some may question the necessity of the assessment and start-up costs, many, if not all, of these small independent practices had no performance data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fi nding is consistent with a prior estimate by Hogg and colleagues for a facilitation intervention to improve preventive services. 12 Approximately 47% of the total practice facilitation costs were attributable to practice assessment and start-up activities, with another 25% attributable to facilitation visits. Although some may question the necessity of the assessment and start-up costs, many, if not all, of these small independent practices had no performance data.…”
Section: Discussionmentioning
confidence: 99%
“…Developing cost estimates associated with administering a practice facilitation program in local or regional primary care settings is necessary to be able to plan for the supporting infrastructure. 12 The purpose of this article is to report the variable costs (those costs that occurred while carrying out all practice facilitation activities) of providing prac- …”
mentioning
confidence: 99%
“…Hogg et al 49 analyzed the overall cost-effectiveness of their similar intervention, finding that, despite the high cost of facilitation, considering the increased rate of delivery of key preventive services the intervention was cost-effective. Six months was barely enough time to effect these changes in most of our practices.…”
Section: Discussionmentioning
confidence: 99%
“…However, Hogg et al 6 recently demonstrated that outreach facilitation is an expensive, but cost-effective way to improve the quality of preventive medicine in primary care. In this study, the cost of a facilitator was offset by the reduction in inappropriate testing and increase in appropriate services, producing a net cost savings.…”
Section: Cost-effectivenessmentioning
confidence: 99%